Spider-Man : face-to-face with the Lizard! - Quantz, Daniel (Spider-Man series, 2006)
Spider-Man travels to Florida to battle the Lizard, a half-man, half-alligator, but after learning the story of how the creature came into existence, he decides a different type of help is needed.